2022
DOI: 10.2334/josnusd.21-0420
|View full text |Cite
|
Sign up to set email alerts
|

A survey of oral health status, subjective oral symptoms and oral health behaviors among first-year dental students at a Japanese university

Abstract: Purpose:The rapid deterioration of oral health in young adults is an alarming problem in Japan. The aim of the present study is to investigate the oral health status, subjective oral symptoms and oral health behaviors of dental students. Methods: Participants were 108 first-year students attending dental school in 2018-2019. Oral examinations were performed to assess dental caries indices, oral hygiene status, gingival bleeding on probing (BOP) and pocket depth. A self-administered questionnaire was used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
1
3
2
Order By: Relevance
“…Similarly, the univariate analysis revealed that the tooth brushing was signi cantly more among NQC than QC. Although it is a foregone conclusion that good oral heath practices are protective against dental caries [30,31], the multivariate analysis didn't support this in our study. Taken together con rms, at least theoretically, that qat chewing negatively nulli es the positive effects of these factors.…”
Section: Discussioncontrasting
confidence: 84%
“…Similarly, the univariate analysis revealed that the tooth brushing was signi cantly more among NQC than QC. Although it is a foregone conclusion that good oral heath practices are protective against dental caries [30,31], the multivariate analysis didn't support this in our study. Taken together con rms, at least theoretically, that qat chewing negatively nulli es the positive effects of these factors.…”
Section: Discussioncontrasting
confidence: 84%
“…Similarly, the univariate analysis revealed that the tooth brushing was significantly more among NQC than QC. Although it is a foregone conclusion that good oral heath practices are protective against dental caries [ 31 , 32 ], the multivariate analysis didn’t support this in our study. Taken together confirms, at least theoretically, that qat chewing negatively nullifies the positive effects of these factors.…”
Section: Discussioncontrasting
confidence: 77%
“…2 Other studies investigating xerostomia among dentistry students also found that majority of their student have some form of xerostomia. 4,6 We also observed that medical and dentistry students have similar pattern of depression and anxiety where the severe symptoms only reported by the smallest percentage of students. Knipe et al also compared among medical and dentistry students but found that dentistry students have higher depression and anxiety risk.…”
Section: Discussionsupporting
confidence: 63%
“…5,6 Xerostomia has been known to poses some risks to gingivitis in young adults. 4,7,8 This study was conducted to investigate whether symptoms of depression, anxiety and stress correlates with symptoms of xerostomia among young adults attending medical and dentistry school.…”
Section: Introductionmentioning
confidence: 99%